WORK MOTIVATION AS MEDIATOR: THE DIFFERENTIAL IMPACT OF EMPLOYEE COMPETENCE AND WORK FACILITIES ON EMPLOYEE PERFORMANCE AT KSOP CLASS III TANJUNG PAKIS - Setia Indarto; Sri Rahayu; Rifda Fitrianty (Journal Informatic, Education and Management (JIEM), 2026)
Public sector maritime bureaucracies face persistent performance gaps despite substantial infrastructure investments, yet the relative effectiveness of human versus physical resources remains contested. This study examines the differential effects of employee competence and work facilities on employee performance through the mediating mechanism of work motivation at KSOP Class III Tanjung Pakis, Indonesia. Using cross-sectional survey data from all employees and Partial Least Squares Structural Equation Modeling with SmartPLS, the analysis reveals asymmetric pathways: competence significantly influences both work motivation and performance, while work facilities demonstrate non-significant effects on both motivation and performance. Work motivation significantly predicts performance and partially mediates the competence-performance relationship, yet completely fails to mediate the facilities-performance pathway. These findings support a hierarchical resource model wherein personal resources activate motivational processes and directly enhance task execution, whereas contextual resources function merely as baseline hygiene conditions. The study extends Self-Determination Theory and Job Demands-Resources Theory by demonstrating that resource type determines psychological mechanism activation in specialized bureaucratic contexts. Practically, results redirect resource allocation priorities toward competence development over infrastructure expansion, offering empirically grounded guidance for public sector human resource management in developing economies.